Childhood conditions and mental health among youth and young adults in Greenland: a latent class analysis - Charlotte Brandstrup Ottendahl; Peter Bjerregaard; Durita Lyngsø Svartá; Ivalu Katajavaara Seidler; Ingelise Olesen; Martine Stecher Nielsen; Christina Viskum Lytken Larsen (International Journal of Circumpolar Health)
Poor mental health among youth in Greenland is a major challenge, childhood conditions are critical for mental health later in life. The study aimed to examine the clustering of childhood conditions by considering risk and protective factors for mental health among youth and young adults in Greenland and to explore the relationship between these clusters and mental health outcomes in youth. The study included 565 participants aged 15–34 living in Greenland. Seven indicators including childhood adversities (ACEs), childhood residence, language, and cultural indicators (protective factors) were used to define clusters via latent class analysis (LCA). The associations between clusters and mental health outcomes (satisfaction with life (Cantrill’s ladder), self-esteem, self-efficacy, loneliness, psychological distress (General Health Questionnaire) and mental illness (Kessler 6)) were assessed by logistic regression. Four clusters were identified through LCA. While most participants reported positive childhoods, 40% (in two clusters) experienced ACEs. The two clusters differed as more participants in one cluster had experienced protective factors than the other. ACEs were associated with increased odds of negative aspects of mental health in youth. However, participants who faced high levels of adversity and few protective factors also had reduced odds of positive aspects of mental health in youth.